2020
DOI: 10.31223/osf.io/cs3tp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping invasive Lupinus polyphyllus Lindl. in semi-natural grasslands using object-based analysis of UAV-borne images

Abstract: Knowledge on the spatio-temporal distribution of invasive plant species is vital to maintain biodiversity in grasslands which are threatened by the invasion of such plants and to evaluate the effect of control activities conducted. Manual digitising of aerial images with field verification is the standard method to create maps of the invasive Lupinus polyphyllus Lindl. (Lupine) in semi-natural grasslands of the UNESCO biosphere reserve “Rhön”. As the standard method is labour- and time-intensive, a workflow wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Other related foci included testing different vegetation indices or structural layers (i.e. DSM or CHM) to improve classifications (Kedia et al, 2021;Lopatin et al, 2019;Martin et al, 2018;Müllerová et al, 2017;Wijesingha et al, 2020). For example, Kedia et al found the inclusion of canopy structural information from the DSM and CHM improved overall classification accuracy for multiple invasive species by 13%, while Marzialetti et al (2021) found the inclusion of the DSM improved mapping accuracy of golden wreath wattle (Acacia saligna) by more than 3%.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other related foci included testing different vegetation indices or structural layers (i.e. DSM or CHM) to improve classifications (Kedia et al, 2021;Lopatin et al, 2019;Martin et al, 2018;Müllerová et al, 2017;Wijesingha et al, 2020). For example, Kedia et al found the inclusion of canopy structural information from the DSM and CHM improved overall classification accuracy for multiple invasive species by 13%, while Marzialetti et al (2021) found the inclusion of the DSM improved mapping accuracy of golden wreath wattle (Acacia saligna) by more than 3%.…”
Section: Methodsmentioning
confidence: 99%
“…Since most camera manufacturers do not specify the wavebands comprising each image channel (Mathews, 2015), camera calibrations are highly recommended. Yet just under 6% of the studies we reviewed articles mentioned calibration, and there was typically very little description of how calibration was accomplished (Michez et al, 2016;Wijesingha et al, 2020). Calibration can be achieved with a highly reflective white reflectance panel designed to give near-perfect diffuse reflectance (Singh, 2021) from which image reflectance values can be standardized and adjusted.…”
Section: Sensor Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other side, technical constraints of UAVs (e.g., battery capability and surveying restrictions) often prevent the use of this technology to describe ecosystem patterns on a large scale. However, the ability to acquire highly customized data makes UAVs an interesting option to provide accurate maps of local IAS occurrence (e.g., Wijesingha et al, 2020;Marzialetti et al, 2021), supporting satellite detection at wider scales. The contribution of VHR images for aiding IAS satellite detection deserves to be further explored (Elkind et al, 2019;Alvarez-Vanhard et al, 2021).…”
Section: Introductionmentioning
confidence: 99%